Probable first record of a drinking seedsnipe (Family Thinocoridae) in the wild - Edelaar, Pim (2005)
Seedsnipes (family Thinocoridae, genera Attagis and Thinocorus with two species each) are strictly vegetarian shorebirds occurring in some of the coldest and driest habitats of southern South America. It has been hypothesised that they retrieve all their water from their food, mostly leaves and buds from (succulent) plants. According to Fjeldså (1996), none of the seedsnipes “are known to drink in natural conditions. However, they may do so in captivity.” In apparent contradiction, he also shows a photograph of a male Greybreasted seedsnipe Thinocorus orbignyianus leaning over at the edge of a pond suggesting that it may have been drinking. Therefore it is not completely sure if drinking in the wild never occurs.